Responding Households to Its Role as a Support for the Family Economy in RW 17 (Kampung KB Bangau Putih) Parupuk Tabing, Padang City - Anita Rahmadani; Wirdatul Aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This research is motivated by the number of housewives who work outside of homework. This study aims to reveal how the housewife's response to her role as a supporter of the family economy in RW 17 (Kampung KB Bangau Putih) Parupuk Tabing Village, namely: 1) in terms of position namely the position of housewives in terms of individuals, law, social society, religion and culture, 2) in terms of actions that are rational actions, value-oriented actions, affective actions, and traditional actions, and 3) in terms of behavior that is based on awareness, and feel attracted as a supporter of the family economy. This type of research is a quantitative descriptive study with a population of housewives who work outside of household workers, amounting to 96. Samples were taken as much as 30% of the population so as to get 30 people. The sampling technique used in this study is Stratified random sampling. Techniques for collecting data use a questionnaire and data collection tools in the form of a statement list. While the data analysis technique uses the percentage formula. The results of this study according to housewives showed a) The description of the responses of housewives to their role in terms of their position as supporting the family economy in RW 17 (Kampung KB Bangau Putih) Parupuk Tabing Village, Padang City was categorized as good. b) The description of the response of a housewife to her role in terms of actions as a support for the family economy in RW 17 (Kampung KB Bangau Putih) Parupuk Tabing Village, Padang City is categorized as good. c) The description of the response of housewives to their role in terms of behavior as a supporter of the family economy in RW 17 (Kampung KB Bangau Putih) Parupuk Tabing Village, Padang City is categorized as good. Suggestions for the head of the household are expected later this research should be able to be a motivation especially for the head of the household/husband to be able to work with his wife in sustaining the family economy. And for families so that this research should be an encouragement for all family members to work together in increasing family income, alleviating the burden on their husbands, and meeting all family needs.Keywords: Responses, Housewives